The Black Indian in American Literature - Byars-Nichols, K. author. aut Link
VIII, 129 p. 2 illus.
Keywords: The first book-length study of the figure of the black Indian in American Literature, this project explores themes of nation, culture, and performativity. Moving from the Post-Independence period to the Contemporary era, Byars-Nichols re-centers a marginalized group challenges stereotypes and conventional ways of thinking about race and culture.